(3aj GdKbGaI GdEbJUGOjI ddeYde (B:s (3CSS fXQjI(B- (3feGPL JOQjHjI(B- (3JWHjbGJ YGdejI (B/s - (3jGSjf, efGd eMeO cGeds; (3eMeO, eUWai YHO GdSejY s ((3GdbGgQI(B: s (3GdecJHI GdYUQjI ddfTQ hGdJhRjY(B, s, 2009)
(3jVe GJaGbjGJ GdLGJ hefXeI GdJLGQI GdYGdejI, GdJcJdGJ GdEbJUGOjI GdYGdejI hGdJcGed GdEbJUGOj GdYQHj, GdJLGQI GdEdcJQhfjI, GdEjRh hEOGQI GdLhOI GdTGedI, HhQUI GdGhQGb GdeGdjI, GdHfhc, Odjd GdeYdes
(3GdeQGLY U(B.228s
Keywords: (3GdJYdje(B- (3GbJUGOjGJs; (3GdJfejI GdEbJUGOjIs; (3GdKbGaI(B- (3GbJUGOs